Development of GoGeo Learning Media to Increase The Ability of Geometry Knowledge of Early Children in TK Negeri Pedesaan - Vera Dewi, Ayu; Priyanti, Nita (Kirana Publisher (KNPub), 2024)
This research aims to develop GoGeo media as a learning medium to improve the ability of early childhood in understanding geometry, resulting in GoGeo media that is suitable for study by Group A students or children aged 4-5 years. This research adopts a modified 4D R&D model according to the needs of researchers and is carried out in one trial, namely a small-scale field trial. The subjects of this study were 10 students of Group A at TK Negeri Pedesaan Kota Serang. The feasibility of GoGeo media is based on the results of validation by three media experts, principals and teachers, as well as Group A students as trial subjects. Data were collected using instruments in the form of questionnaires, interviews, observations and documents. Data analysis used qualitative data analysis and quantitative data analysis. The results showed that the developed GoGeo media after a series of experiments and expert validation was considered good and very good. This is supported by the assessment of media experts obtaining scores of 81.33 points, 92 points, and 90.67 points in the good and very good categories, assessment of principals and teachers with an average score of 5 included in the very good category, small-scale trials getting the BSH and BSB categories. The results of the child's response test to the GoGeo media were 82 points out of 90 with a passing rate of 91.11%. So it can be concluded that the GoGeo media is